2004
DOI: 10.1016/j.accreview.2004.07.113
|View full text |Cite
|
Sign up to set email alerts
|

Serum total homocysteine concentrations and risk of stroke and its subtypes in Japanese

Abstract: Background-To date, no prospective studies have examined the association between serum homocysteine levels and the risk of stroke and stroke subtypes in Asian populations. Methods and Results-A prospective, nested, case-control study of Japanese subjects 40 to 85 years of age was conducted by using frozen serum samples from 11 846 participants in cardiovascular risk surveys collected from 1984 to 1995 for one community and 1989 to 1995 for the other two communities. By the end of 2000, we identified 150 incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…Furthermore, on subgroup analysis based on gender, significantly higher homocysteine levels were seen in male stroke patients as compared to control males (19.94±8.91 vs. 10.56±4.41, p<0.01) as well as in female stroke patients as compared to control females (19.75±8.65 vs. 10.33±4.54, p<0.01). Our findings are in agreement with results of previous studies done to evaluate the role of Homocysteine as a risk factor for stroke in different demographic populations [10][11][12][13][14]. In a nested case-control study done prospectively within the British Regional Heart Study cohort, Perry et al evaluated the relation between serum total homocysteine level (tHcy) and risk of stroke in the middle-aged British men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, on subgroup analysis based on gender, significantly higher homocysteine levels were seen in male stroke patients as compared to control males (19.94±8.91 vs. 10.56±4.41, p<0.01) as well as in female stroke patients as compared to control females (19.75±8.65 vs. 10.33±4.54, p<0.01). Our findings are in agreement with results of previous studies done to evaluate the role of Homocysteine as a risk factor for stroke in different demographic populations [10][11][12][13][14]. In a nested case-control study done prospectively within the British Regional Heart Study cohort, Perry et al evaluated the relation between serum total homocysteine level (tHcy) and risk of stroke in the middle-aged British men.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with control subjects, total (n=150), hemorrhagic (n=52), and ischemic (n=98) strokes had higher geometric mean values of total homocysteine. They concluded that high total Homocysteine levels were associated with the increased risk of stroke, more specifically ischemic stroke and lacunar infarction, among Japanese men and women [11]. In an Indian study, Narang et al evaluated the role of homocysteine as a risk factor for ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] A higher dietary intake of folate has been associated with lower risk of incident stroke and mortality from stroke, coronary heart disease, and heart failure. [8][9][10][11] Furthermore, Okinawan vegetables contain several functional substances that have been indicated to affect health in the molecular level. For example, bitter gourds have demonstrated antioxidant activities in both in vivo and in vitro experi-ments 12 and can decrease low-density lipoprotein cholesterol and triglyceride levels, suppress visceral fat accumulation, and inhibit adipocyte hypertrophy in diet-induced obese rats and mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that elevated plasma homocysteine concentration is a potential risk factor for arterial sclerosis and cardiovascular diseases (Boushey and others 1995; Mayer and others 1996; Duell and Malinow 1997; Pietrzik and Bronstrup 1997; Selhub 1999). Hyperhomocysteinemia is related to the incidence of neural tube defects (NTDs) in fetus, Alzheimer dementia, Parkinson's disease, and cancer (Mattson and others 2002; Seshadri and others 2002; Wu and Wu 2002; Leboeuf 2003; Iso and others 2004). Therefore, dietary control of homocysteine levels has been attempted.…”
Section: Introductionmentioning
confidence: 99%